Pilomyxoid astrocytoma of the corpus callosum presenting with primary haemorrhage in an adolescent - Longo, Maria Gabriela Figueiró (2017)
A 17-year-old male patient with history of intraventricular haemorrhage in 2007 underwent a brain MRI scan in 2013 owing to headache. Brain MRI scan showed an expansive lesion adjacent to the left lateral ventricle infiltrating the anterior portion of the corpus callosum. After surgery, pathology confirmed a pilomyxoid astrocytoma (PMA), an aggressive subtype of astrocytoma that occurs predominantly in the hypothalamic-chiasmatic region. On imaging, PMA presents as a tumour isointense on T1, hyperintense on T2 that enhanced heterogeneously with contrast. The T2 signal is higher than pilocytic astrocytoma, which indicates the presence of myxoid matrix. These findings on MRI scan have a direct correlation with a specific pathological finding — monomorphic proliferation of piloid cells in a mucopolysaccharide-rich matrix. These characteristics associated with the absence of Rosenthal fibres or eosinophilic granules indicated the diagnosis of PMA. To our knowledge, this is the first case report of PMA affecting the corpus callosum in an adolescent.